Postpartum Tuberculosis: A Diagnostic and Therapeutic Challenge - Vijay Kodadhala; Alemeshet Gudeta; Aklilu Zerihun; Odene Lewis; Sohail Ahmed; Jhansi Gajjala; Alicia Thomas (Case Reports in Pulmonology)
Tuberculosis (TB) infection in pregnant women and newborn babies is always challenging. Appropriate treatment is pivotal to curtail morbidity and mortality. TB diagnosis or exposure to active TB can be emotionally distressing to the mother. Circumstances can become more challenging for the physician if the mother’s TB status is unclear. Effective management of TB during pregnancy and the postpartum period requires a multidisciplinary approach including pulmonologist, obstetrician, neonatologist, infectious disease specialist, and TB public health department. Current guidelines recommend primary Isoniazid prophylaxis in TB exposed pregnant women who are immune-suppressed and have chronic medical conditions or obstetric risk factors and close and sustained contact with a patient with infectious TB. Treatment during pregnancy is the same as for the general adult population. Infants born to mothers with active TB at delivery should undergo a complete diagnostic evaluation. Primary Isoniazid prophylaxis for at least twelve weeks is recommended for those with negative diagnostic tests and no evidence of disease. Repeated negative diagnostic tests are mandatory before interrupting prophylaxis. Separation of mother and infant is only necessary when the mother has received treatment for less than 2 weeks, is sputum smear-positive, or has drug-resistant TB. This case highlights important aspects for management of TB during the postpartum period which has a higher morbidity. We present a case of a young mother migrating from a developing nation to the USA, who was found to have a positive quantiFERON test associated with multiple cavitary lung lesions and gave birth to a healthy baby.